Characterization of Canberra BE3825 Broad Energy High Purity Germanium Detector by means of GEANT4 Monte Carlo calculations - Patronis, N.; Tsamis, V.; Stamoulis, K.; Ioannides, K. G. (HNPS Advances in Nuclear Physics, 2019)
The Canberra BE3825 Broad Energy High Purity Germanium Detector facilitates the detection of -rays from a few keV up to the MeV energy region. Phenomena like self-attenuation and/or coincidence summing e↵ects are hindering the detection of low energy gamma-rays in those cases where extended sources, particu- larly high volume sources are considered. In order to make corrections accordingly, the full characterisation of the HPGe detector is needed. In the present work the Geant4 modeling of the University of Ioannina BE3825 HPGe -ray measuring station is described. The Monte Carlo simulation results are compared with the experimental eciency curves at two di↵erent source to detector distances. In both cases excellent agreement with the experimental results was obtained.